PENGGUNAAN LIMBAH SABUN SC-88 SEBAGAI PUPUK DALAM USAHATANI PETSAI - Said Masduki (Universitas Tribhuwana Tunggadewi, 2008)
A demonstration plot on the use of SC-88 soap waste as manure for planting petsai (Brassica chinensis) had been conducted at Tlogomas village, Lowokwaru regency of Malang for 6 month by involving farmers of Barokah Farmer Group of Tlogomas village and extention workers of Malang Agricultural Board in the form of discussion and excursion on the demonstration plot. Results of this activity showed that all farmers of the Barokah Farmer Group were interested in the use of SC-88 soap waste as manure for planting petsai. Extension workers of Malang Agricultural Board will develop the use of SC-88 soap waste as manure for planting petsai as one of their extension course materials. Petsai planted in a 6 m2 field yielded 14 kg of petsai. This will give income that ranged from Rp.35.0000 to Rp. 56.000